1986
DOI: 10.1128/mcb.6.8.2957
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a novel high-affinity purine nucleobase transport function in mutant mammalian T lymphoblasts.

Abstract: The single nucleoside transport function of mouse S49 lymphoblasts also transports purine bases (B. Aronow and B. Ullman, J. Biol. Chem. 261:2014Chem. 261: -2019Chem. 261: , 1986). This transport of purine bases by S49 cells is sensitive to inhibition by dipyridamole (DPA) and 4-nitrobenzylthioinosine, two potent inhibitors of nucleoside transport. Therefore, wild-type S49 cells cannot salvage low hypoxanthine concentrations in the presence of 10 ,uM DPA and 11 ,uM azaserine; the latter is a potent inhibitor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Genetic studies in S49 cells have demonstrated a role of the nucleoside transport system in mediating the permeation of purine bases across the plasma membrane (3,4,6). Nucleoside transport-deficient S49 cell lines have been generated which transport hypoxanthine and adenine at lower rates than wild-type parental cells (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies in S49 cells have demonstrated a role of the nucleoside transport system in mediating the permeation of purine bases across the plasma membrane (3,4,6). Nucleoside transport-deficient S49 cell lines have been generated which transport hypoxanthine and adenine at lower rates than wild-type parental cells (6).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of either DPA or NBMPR prevents wild-type S49 cells from salvaging low concentrations of hypoxanthine in the presence of an inhibitor of purine biosynthesis (6). However, rare mutants can be isolated from wild-type cells that are capable of proliferation in medium containing hypoxanthine, azaserine, and DPA (4). These cells express a high-affinity transport system for hypoxanthine, guanine, and adenine, which can be differentiated from the wild-type nucleoside-nucleobase carrier by a variety of biochemical criteria.…”
mentioning
confidence: 99%
“…Purine-selective nucleobase transporters have also been described in mammalian erythrocytes, T-lymphoblast JPA2, CCRF-CEM, OK, primary human cardiac microvascular endothelial cells, and LLC-PK1 cells (1,4,12,13,19). Although none of these nucleobase transporters is shown to transport nucleosides, adenosine inhibits […”
Section: Discussionmentioning
confidence: 99%
“…The former is inhibited by purine nucleosides and nucleobases but not by pyrimidines, and the latter is inhibited by pyrimidine nucleosides and nucleobases but not by purines. An Na-independent nucleobase transport has been reported in human erythrocytes, JAP2, CCRF-CEM, primary human cardiac microvascular endothelial cells, and LLC-PK1 cells (1,(12)(13)(14)(15)(16)(17). The affinities of adenine, guanine, and hypoxanthine for the Na-independent nucleobase transport system are 13-30 M, 18 -37 M, and 90 -120 M, respectively (4,14).…”
mentioning
confidence: 99%
“…Intestinal alkaline phosphatase (ALP) cleaves the phosphate group from the ribonucleotides to form ribonucleosides, and intestinal ribonucleotidases and ribonucleosidases produce free purine and pyrimidine bases [2,3]. Ribonucleosides and their nucleobases are translocated across the plasma membrane by specified facilitated-diffusion carriers and sodium dependent transporters [4][5][6][7][8][9][10][11][12][13] located in intestinal and kidney epithelial cells [14][15][16][17][18][19][20]. It has been demonstrated that ribonucleotides and related compounds are semi-essential [21].…”
Section: Introductionmentioning
confidence: 99%